Large-Area SiPM Pixels (LASiPs) in SPECT. (1st July 2022) - Wunderlich, C.; Guberman, D.; Paoletti, R.; Rugliancich, A.; Passeri, A.
Abstract: A standard camera for Single Photon Emission Computed Tomography (SPECT) contains 50–100 photomultiplier tubes (PMTs) that occupy at least 50% of its volume. It is shielded by a thick layer of lead which makes it heavy and bulky. Replacing PMTs by silicon photomultipliers (SiPMs) could significantly reduce the weight and size of a SPECT camera. However, the main obstacle is the limited size of SiPMs: even with the largest commercially available SiPM of 6 × 6 mm 2 a few thousand channels would be needed to fill a camera. As a solution, we propose to use Large Area SiPM Pixels (LASiPs) which are built by summing the currents of several SiPMs into a single output. We developed a LASiP prototype summing 8 SiPMs using the MUSIC ASIC. To test the feasibility of using this solution in SPECT, we built a proof-of-concept micro camera that consisted of four of our LASiP prototypes coupled to a 40 × 40 × 8 mm 3 NaI(Tl) crystal. We were able to reconstruct simple images of a 99 m Tc capillary with an intrinsic spatial resolution of ∼2 mm and an energy resolution of ∼11.6%. We also simulated the system with Geant4, finding a good agreement with our experimental results. The simulations were extended to a larger camera, aiming to study the impact of pixel size, shape and noise.